Synthesis method of triazinyl polymer for rechargeable battery electrode active material
By performing ion-thermal Friedel-Crafts reaction in eutectic salts and using an inorganic salt system as solvent and catalyst, the problem of using harmful solvents and limited compatibility in the existing methods is solved, and the efficient synthesis of triazine-based polymers is achieved. High electrochemical properties and long cycle life.
Patent Information
- Application Number
- CN202411622340.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Friedel-Crafts reaction methods require the use of harmful alkyl halide solvents when preparing triazine-based polymers, and their compatibility with comonomers is limited, limiting the possibility of efficient synthesis.
The method of ion-thermal Friedel-Crafts reaction is carried out in AlCl3-NaCl-KCl or FeCl3-NaCl-KCl eutectic salt, using anhydrous aluminum chloride or anhydrous ferric chloride inorganic form, sodium chloride and potassium chloride. As a solvent and catalyst, the salt system achieves efficient solvent-free synthesis.
This method not only avoids the use of harmful halide solvents, but is also compatible with monomers with low Friedel-Crafts reactive activity, achieving efficient polymerization. The resulting triazine-based polymer has high specific capacity, good rate performance and long cycles life.
Smart Images

Figure CN119463171A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer synthesis and organic battery materials, and in particular relates to a method for preparing an active material for a rechargeable battery electrode. Background Art
[0002] In recent years, with the rapid development of renewable and intermittent energy technologies such as solar energy, wind energy, and tidal energy, the global society has an increasing demand for large-scale electrochemical energy storage. Although lithium-ion batteries (LIBs) have dominated the portable electronics and electric vehicle markets, the low abundance and uneven distribution of cobalt, nickel, and lithium resources in the earth's crust have prevented LIBs from being more widely used in large-scale energy storage. Therefore, both academia and industry are committed to developing rechargeable batteries that rely on low-cost and abundant elements, such as rechargeable aluminum metal batteries, sodium-ion batteries, and aqueous zinc metal batteries. In particular, the use of organic electrode materials composed of elements such as C, H, N, and O in the above batteries is more promising for realizing electrochemical energy storage technologies with sustainable development characteristics. In the past few years, triazine-based polymers have attracted widespread attention as electrode materials for various rechargeable batteries. Using Lewis acids (such as ZnCl 2 , FeCl 3 , AlCl 3 ) or strong The acid-catalyzed Friedel-Crafts reaction is a simple, easy-to-operate and efficient method for preparing triazine-based polymers. However, the Friedel-Crafts reaction usually uses alkyl / aryl halides as inert solvents, such as dichloromethane, dichloroethane, chloroform, 1,2-dichlorobenzene, etc., which seriously damage the ecological environment, thus limiting its large-scale application. More importantly, during the Friedel-Crafts reaction, when alkyl halide solvents are used, Friedel-Crafts alkylation also occurs as a side reaction, thereby forming a non-conjugated structure with low electrochemical activity in the polymer structure. Recently, a mechanochemical Friedel-Crafts reaction can prepare three high-yield triazine-based polymers. These three polymers are respectively prepared by carbazole, anthracene and triphenylbenzene as comonomers of cyanuric chloride, providing a solvent-free synthesis method. However, this method can only prepare triazine-based conjugated polymers by polymerization reaction with monomers with higher Friedel-Crafts reaction activity as comonomers of cyanuric chloride. Therefore, further exploration of green and efficient Friedel-Crafts reaction methods that avoid the use of organic halide solvents and are compatible with a variety of different types of comonomers is crucial for the efficient synthesis of triazine-based polymers. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing a 3 -NaCl-KCl or FeCl 3 -NaCl-KCl eutectic salt to prepare triazine-based polymers by ionothermal Friedel-Crafts reaction synthesis method, wherein the eutectic salt with low eutectic point makes this method an economical and efficient Lewis acid solvent-catalyst system. In addition, the monomers of this method are widely applicable, and even monomers with low Friedel-Crafts reactivity can undergo efficient polymerization reaction; in addition, this method does not require halogenated solvents, the synthesis process is green and environmentally friendly, and the cost is low. The prepared triazine-based polymer can be used as an electrode active material for rechargeable batteries, and has the characteristics of high specific capacity, good rate performance and long cycle life.
[0004] To achieve the above-mentioned purpose, the present invention provides a method for synthesizing a triazine-based polymer, which comprises the following steps: mixing cyanuric chloride and an aromatic compound, anhydrous aluminum chloride or anhydrous ferric chloride, sodium chloride and potassium chloride under a nitrogen atmosphere, and heating the mixture at 100 to 180° C. for reaction for 24 to 72 hours; cooling the mixture to room temperature after the reaction is completed, washing the mixture with concentrated hydrochloric acid, water and methanol respectively, extracting the mixture by reflux with tetrahydrofuran, and then vacuum drying the mixture to obtain a triazine-based polymer.
[0005] In the above synthesis method, the aromatic compound includes any one of benzene, toluene, biphenyl, naphthalene, pyrene, carbazole, perylene, N-methyldiphenylamine, 10-methyl-10-hydrophenothiazine, phenothiazine, 5,10-dihydro-5,10-dimethylphenazine, tetrakis-N-phenyl-p-phenylenediamine and phenoxazine, etc. The aromatic compound includes but is not limited to the above compounds, and can be easily expanded to other aromatic compounds.
[0006] In the above synthesis method, the molar ratio of cyanuric chloride to aromatic compound is 1:0.2-2, and the ratio is regulated according to the structural characteristics of the monomer. When the molar ratio of cyanuric chloride to aromatic compound changes, the connection sites and number of aromatic compounds in the triazine-based polymer will change accordingly, which can be understood and controlled by those working in the field of polymer synthesis.
[0007] In the above synthesis method, the molar ratio of cyanuric chloride to anhydrous aluminum chloride or anhydrous ferric chloride is preferably 1:2.5-7.5, and the molar ratio of cyanuric chloride to anhydrous aluminum chloride or anhydrous ferric chloride is more preferably 1:4-6.
[0008] In the above synthesis method, the molar ratio of anhydrous aluminum chloride to sodium chloride and potassium chloride is preferably 1:0.3-0.7:0.1-0.4, and the molar ratio of anhydrous aluminum chloride to sodium chloride and potassium chloride is further preferably 1:0.4-0.5:0.2-0.3.
[0009] In the above synthesis method, the molar ratio of the anhydrous ferric chloride to sodium chloride and potassium chloride is preferably 1:0.5-0.8:0.2-0.4.
[0010] In the above-mentioned synthesis method, the reaction is preferably heated at 130 to 160° C. for 48 to 60 hours.
[0011] In the above synthesis method, the triazine-based polymer prepared is a cross-linked polymer.
[0012] The beneficial effects of the present invention are as follows:
[0013] 1. The synthesis method of the triazine-based polymer of the present invention is based on the Friedel-Crafts reaction, and the raw materials are cheap and readily available. The ionothermal synthesis method uses an inorganic salt mixed with anhydrous aluminum chloride or anhydrous ferric chloride, sodium chloride and potassium chloride as a solvent and a catalyst, so the synthesis method of the present invention has the characteristics of simple process and green environmental protection.
[0014] 2. The inorganic salt solvent-catalyst system used in the synthesis method of the present invention has less restriction on the range of monomers, and is still compatible with monomers with low activity in Friedel-Crafts reaction and can achieve a higher yield.
[0015] 3. The triazine-based polymer prepared by the synthesis method of the present invention can be used as both a positive electrode material and a negative electrode material of a rechargeable battery. When the triazine-based polymer is used as a positive electrode active material of a rechargeable battery, during the charging process, the macromolecular chain of the triazine-based polymer is oxidized to lose electrons, forming positively charged cationic free radicals; in the subsequent discharge process, the positively charged cationic free radicals generated on the polymer macromolecular chain accept electrons and are reduced to the initial neutral state, and release the stored anions into the electrolyte, thereby achieving a reversible electrochemical reaction and having a high specific capacity. When the triazine-based polymer is used as a negative electrode active material of a rechargeable battery, during the discharge process, the macromolecular chain of the triazine-based polymer is reduced to accept electrons and form negatively charged anionic free radicals; in the subsequent charging process, the negatively charged anionic free radicals generated on the macromolecular chain of the triazine-based polymer lose electrons and are oxidized to the initial neutral state, and release the stored cations into the electrolyte. Based on the above reaction principles and characteristics, a rechargeable battery with high capacity and good rate performance is finally obtained.
[0016] 4. The triazine-based polymer synthesized by the method of the present invention has a highly cross-linked molecular structure. The presence of the triazine structure ensures the high electrochemical activity of the synthesized polymer; the highly cross-linked molecular structure can effectively inhibit the dissolution of the synthesized polymer in most solvents, effectively solving the dissolution problem of small molecules or linear polymers in ionic electrolytes, thereby improving the cycle stability of the battery and facilitating the realization of a long cycle life; the rich monomer types enable the structure, composition and electrochemical properties of the synthesized polymer to be adjusted through the structure of the monomer. Thanks to the unique advantages of the above-mentioned synthesis method and the excellent electrochemical properties of the triazine-based polymer, the designed and developed synthesis method of the triazine-based polymer is expected to provide technical support for the commercialization of rechargeable batteries based on polymer electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the infrared spectrum of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0018] Figure 2 This is the solid state carbon nuclear magnetic resonance spectrum of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0019] Figure 3 This is the XRD spectrum of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0020] Figure 4 3 is a nitrogen adsorption-desorption curve of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0021] Figure 5 This is the pore size distribution diagram of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0022] Figure 6 This is a scanning electron microscope photograph of the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1.
[0023] Figure 7 The cyclic voltammetry curve of the aluminum battery prepared by using the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1 as the positive electrode active material.
[0024] Figure 8 It is the constant current charge and discharge curve of the aluminum battery prepared by using the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1 as the positive electrode active material.
[0025] Fig. 9The figure is the rate performance of an aluminum battery prepared using the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1 as the positive electrode active material.
[0026] Fig.10 The cycle performance of the aluminum battery prepared using the triazine-based polymer copolymerized with cyanuric chloride and 10-methyl-10-hydrophenothiazine in Example 1 as the positive electrode active material.
[0027] Fig.11 It is the infrared spectrum of the triazine-based polymer synthesized in Examples 2 to 8.
[0028] Fig.12 It is the XRD spectrum of the triazine-based polymer synthesized in Examples 2 to 8.
[0029] Fig.13 It is a nitrogen adsorption-desorption curve diagram and pore size distribution diagram of the triazine-based polymer synthesized in Examples 2 to 8.
[0030] Wherein (a) to (g) are the results of Examples 2 to 8 respectively.
[0031] Fig.14 These are scanning electron microscope photographs of the triazine-based polymers synthesized in Examples 2 to 8. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0033] Example 1
[0034] Under nitrogen atmosphere, 590 mg (2.766 mmol) of 10-methyl-10-hydrophenothiazine and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting black solid powder was a triazine-based polymer.
[0035] Using infrared spectroscopy and 13The chemical structure of the obtained triazine-based polymer was characterized by C solid-state NMR spectroscopy. Figures 1-2 . Figure 1 The infrared spectrum of the sample showed characteristic peaks of both 10-methyl-10-hydrophenothiazine and triazine units. These peaks included the peaks of CS and CN in the 10-methyl-10-hydrophenothiazine unit at about 1133 cm -1 and 1267cm -1 The stretching vibration signal of the triazine ring at about 1454 cm -1 and 1337cm -1 Vibration bands at . Figure 2 Triazine-based polymer 13 C solid NMR spectrum, the peak at the chemical shift of 169.5 ppm comes from the carbon atom in the triazine ring, and the peak at about 143.3 ppm can be attributed to the carbon atom connected to the N atom in the 10-methyl-10-hydrophenothiazine unit. In addition, the peak at a low chemical shift of about 34.8 ppm corresponds to the characteristic signal of the methyl carbon atom in the 10-methyl-10-hydrophenothiazine unit. Figure 3 The XRD results showed that the triazine-based polymer was amorphous. The porosity of the triazine-based polymer was characterized by nitrogen adsorption-desorption curve. Figure 4 It can be seen that the specific surface area of the obtained triazine-based polymer is 7.3 m 2 g -1 . Figure 5 The pore size distribution results show that the triazine-based polymer has a multi-level pore structure. Figure 6 is a scanning electron microscope photograph of the triazine-based polymer, which shows a blocky morphology.
[0036] The triazine-based polymer synthesized in this embodiment is used as the positive electrode active material of the aluminum battery. The specific method is as follows: the triazine-based conjugated polymer, carbon black and polyvinylidene fluoride are mixed and ground according to a ratio of 6:3:1, N-methylpyrrolidone is added to disperse them evenly to obtain a uniformly mixed electrode slurry, the slurry is coated on a tungsten mesh, and vacuum dried to prepare a triazine-based polymer positive electrode sheet, wherein the active material loading is 1.70 mg cm -2 The aluminum battery with triazine-based polymer as the positive electrode active material was assembled using a triazine-based polymer positive electrode, an aluminum metal negative electrode, a glass fiber separator, and an aluminum chloride / 1-butyl-3-methylimidazole chloride electrolyte with a molar ratio of 1.3 / 1. The assembled aluminum battery has a voltage range of 0.4-2.05V and a current density of 0.1-20A at 25°C. -1 Carry out constant current charge and discharge test, the test results are shown in Figures 7-10 . Figure 7 The cyclic voltammetry curve results show that the triazine-based polymer positive electrode has obvious redox peaks at 1.45 / 1.26 and 1.87 / 1.80V. Figure 8The constant current charge-discharge curves show that the triazine-based polymer positive electrode has a high -1 The current density was as high as 141.8 mAh g -1 The specific capacity of the battery is 2.4 W, and the charge-discharge voltage platform corresponds to the redox peak potential of the cyclic voltammetry curve. Fig. 9 The rate performance test shows that even at up to 20A -1 At a current of 2.5 200 mAh / s, the triazine-based polymer cathode still has a capacity of 62 mAhg / s. -1 Specific capacity. Fig.10 The cycling performance test shows that the triazine-based polymer positive electrode can be stably cycled 23,000 times. It should be noted that the triazine-based polymer can also be used as a positive electrode or negative electrode material for other secondary batteries.
[0037] Example 2
[0038] Under nitrogen atmosphere, 280 mg (1.383 mmol) of pyrene and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and then the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting reddish brown solid powder was a triazine-based polymer.
[0039] The chemical structure of the obtained triazine-based polymer was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1487 cm -1 and 1354cm -1 There are vibration bands. Fig.12 The XRD results showed that the triazine polymer was amorphous. The porosity of the reddish brown solid powder was characterized by nitrogen adsorption-desorption curve. Fig.13 It can be seen that the specific surface area of the obtained triazine-based polymer is 12 m 2 g -1 , containing some mesopores and macropores. Fig.14 This is a scanning electron microscope picture of the polymer, which shows a blocky morphology.
[0040] Example 3
[0041] Under nitrogen atmosphere, 507 mg (2.766 mmol) of phenoxazine and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting black solid powder was a triazine-based polymer.
[0042] The chemical structure of the obtained triazine-based polymer was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1492 cm -1 and 1352cm -1 There is a vibration band at 1086cm -1 The vibrational band at corresponds to the CO bond of phenoxazine. Fig.12 The XRD results show that the obtained triazine-based polymer is an amorphous structure. The porosity of the triazine-based polymer was characterized by nitrogen adsorption-desorption curve. The results are shown in Fig.13 .Depend on Fig.13 It can be seen that the specific surface area of the obtained triazine-based polymer is 93 m 2 g -1 , mainly containing some mesoporous structures. Fig.14 is a scanning electron microscope photograph of the polymer, which shows a granular morphology.
[0043] Example 4
[0044] Under nitrogen atmosphere, 462 mg (2.766 mmol) of carbazole and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3, 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL of concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting brown solid powder was a triazine-based polymer.
[0045] The chemical structure of the obtained cyanuric chloride was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1487 cm -1 and 1350cm -1 There is a vibration band at 1261cm -1 The vibration band at corresponds to the CN bond of carbazole. Fig.12 The XRD results showed that the triazine-based polymer was amorphous. The porosity of the triazine-based polymer was characterized by nitrogen adsorption-desorption curve. Fig.13 It can be seen that the specific surface area of the obtained triazine-based polymer is 7m 2 g -1 , containing mesoporous and macroporous structures. Fig.14 This is a scanning electron microscope picture of the polymer, which shows a blocky morphology.
[0046] Example 5
[0047] Under nitrogen atmosphere, 582 mg (2.766 mmol) of 5,10-dihydro-5,10-dimethylphenazine and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting black solid powder was a triazine-based polymer.
[0048] The chemical structure of triazine-based polymers was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1467 cm -1 and 1350cm -1 There is a vibration band at 1282cm -1 The vibration band at corresponds to the CN bond of 5,10-dihydro-5,10-dimethylphenazine. Fig.12 The XRD results show that the obtained triazine-based polymer is an amorphous structure. The porosity of the triazine-based polymer was characterized by nitrogen adsorption-desorption curve. The results are shown in Fig.13 .Depend on Fig.13 It can be seen that the specific surface area of the obtained black solid powder is 5m 2 g -1 , containing a multi-level pore structure. Fig.14 is a scanning electron microscope photograph of the polymer, which shows a granular morphology.
[0049] Example 6
[0050] Under nitrogen atmosphere, 348 mg (1.383 mmol) of perylene and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting black solid powder was a triazine-based polymer.
[0051] The chemical structure of triazine-based polymers was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1457 cm -1 and 1341cm -1 There are vibration bands. Fig.12 The XRD results show that the obtained oxazine-based polymer has an amorphous structure. The porosity of the oxazine-based polymer was characterized by nitrogen adsorption-desorption curves. Fig.13 .Depend on Fig.13 It can be seen that the specific surface area of the obtained oxazine-based polymer is 6 m 2 g -1, containing a multi-level pore structure. Fig.14 is a scanning electron microscope photograph of the polymer, which shows a granular morphology.
[0052] Example 7
[0053] Under nitrogen atmosphere, 570 mg (1.383 mmol) of tetra-N-phenyl-p-phenylenediamine and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1230 mg (9.224 mmol) of anhydrous AlCl 3 , 230mg (3.936mmol) NaCl and 146mg (1.95mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 150°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL of concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting red solid powder was a triazine-based polymer.
[0054] The chemical structure of the obtained triazine-based polymer was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1489 cm -1 and 1360cm -1 There is a vibration band at 1240cm -1 The vibration band at corresponds to the CN bond of tetra-N-phenyl-p-phenylenediamine. Fig.12 The XRD results show that the obtained triazine-based polymer is an amorphous structure. The porosity of the triazine-based polymer was characterized by nitrogen adsorption-desorption curve. The results are shown in Fig.13 .Depend on Fig.13 It can be seen that the specific surface area of the obtained red solid powder is 89m 2 g -1 , containing micropores, mesopores and macropores. Fig.14 This is a scanning electron microscope picture of the polymer, which shows a blocky morphology.
[0055] Example 8
[0056] Under nitrogen atmosphere, 280 mg (1.383 mmol) of pyrene and 340 mg (1.844 mmol) of cyanuric chloride were ground together for one minute, and 1490 mg (9.248 mmol) of anhydrous FeCl 3, 394mg (6.743mmol) NaCl and 244mg (3.275mmol) KCl mixture was ground for one minute, then the two mixtures were mixed and ground together for two minutes, and the resulting mixture was placed in a Schlenk tube and heated at 160°C for 48 hours under a nitrogen atmosphere. After the reaction was completed, it was cooled to room temperature, 0.5mL concentrated hydrochloric acid was added to the Schlenk tube and allowed to stand for 6 hours, the precipitate was collected by filtration and washed with water and methanol in turn, and then extracted with tetrahydrofuran Soxhlet for 4 hours. The product was collected and dried in a vacuum oven at 80°C for 24 hours, and then ground in a grinding mortar. The resulting brown solid powder was a triazine-based polymer.
[0057] The chemical structure of the obtained triazine-based polymer was characterized by infrared spectroscopy. Fig.11 . Fig.11 The triazine ring is at about 1479 cm -1 and 1331cm -1 There are vibration bands. Fig.12 The XRD results showed that the obtained triazine-based polymer had a partially ordered stacking structure. The porosity of the brown solid powder was characterized by nitrogen adsorption-desorption curve. Fig.13 It can be seen that the specific surface area of the obtained triazine-based polymer is 20 m 2 g -1 , containing some mesopores and macropores. Fig.14 This is a scanning electron microscope picture of the polymer, which shows a blocky morphology.
Claims
1. A method for synthesizing a triazine-based polymer for a rechargeable battery electrode active material, characterized in that: In a nitrogen atmosphere, cyanuric chloride and aromatic compounds, anhydrous aluminum chloride or anhydrous ferric chloride, sodium chloride and potassium chloride are mixed, and heated at 100-180°C for reaction for 24-72 hours; after the reaction is completed, it is cooled to room temperature, washed with concentrated hydrochloric acid, water and methanol respectively, extracted with tetrahydrofuran reflux, and then vacuum dried to obtain a triazine-based polymer.
2. The method for synthesizing a triazine-based polymer for a rechargeable battery electrode active material according to claim 1, characterized in that: The aromatic compound is selected from any one of benzene, toluene, biphenyl, naphthalene, pyrene, carbazole, perylene, N-methyldiphenylamine, 10-methyl-10-hydrophenothiazine, phenothiazine, 5,10-dihydro-5,10-dimethylphenazine, tetra-N-phenyl-p-phenylenediamine and phenoxazine.
3. The method for synthesizing a triazine-based polymer for a rechargeable battery electrode active material according to claim 1, characterized in that: The molar ratio of the cyanuric chloride to the aromatic compound is 1:0.2-2.
4. The method for synthesizing a triazine-based polymer for an electrode active material of a rechargeable battery according to claim 1, characterized in that: The molar ratio of cyanuric chloride to anhydrous aluminum chloride or anhydrous ferric chloride is 1:2.5-7.
5.
5. The method for synthesizing a triazine-based polymer for an electrode active material of a rechargeable battery according to claim 4, characterized in that: The molar ratio of cyanuric chloride to anhydrous aluminum chloride or anhydrous ferric chloride is 1:4-6.
6. The method for synthesizing a triazine-based polymer for an active material for an electrode of a rechargeable battery according to claim 1, 4 or 5, characterized in that: The molar ratio of the anhydrous aluminum chloride to sodium chloride and potassium chloride is 1:0.3-0.7:0.1-0.
4.
7. The method for synthesizing a triazine-based polymer for an electrode active material of a rechargeable battery according to claim 6, characterized in that: The molar ratio of the anhydrous aluminum chloride to sodium chloride and potassium chloride is 1:0.4-0.5:0.2-0.
3.
8. The method for synthesizing a triazine-based polymer for a rechargeable battery electrode active material according to claim 1, 4 or 5, characterized in that: The molar ratio of the anhydrous ferric chloride to sodium chloride and potassium chloride is 1:0.5-0.8:0.2-0.
4.
9. The method for synthesizing a triazine-based polymer for a rechargeable battery electrode active material according to claim 1, characterized in that: The reaction was heated at 130-160°C for 48-60 hours.